2010
DOI: 10.1590/s0103-50532010000700017
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies of the tautomerism in 3-(2-R-Phenylhydrazono)-naphthalene- 1,2,4-triones: synthesis of copper(II) complexes and studies of antibacterial and antitumor activities

Abstract: Cálculos teóricos utilizando os funcionais B3LYP e PBE1PBE e as bases 6-31G(d) e 6-311+G(2d,p) para o sistema 3-(2-fenil-hidrazona)-naftaleno-1,2,4-triona, em solução (dmso) e em fase gasosa, evidenciaram, em ambos os casos, a maior estabilidade da forma ceto-hidrazona (rotâmeros Ia e Ib) comparada às formas enol-azo (rotâmeros IIa/IIb, por volta de 14 kcal mol -1 ) e III (aproximadamente 6 kcal mol -1 ). A natureza do substituinte no grupo fenil não influenciou a estabilidade relativa dos tautômeros. Estes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The 1,2- and 1,4-naphthoquinone nuclei are commonly encountered in natural products, and their derivatives exhibit a wide range of pharmacological properties including anticancer activities. , Such properties are due to the interference of quinones in the electron transport chain by electron reduction processes, generating semiquinone radical (Q •– ) and hydroquinone anion (Q 2– ). , Incorporation of an azo group into 2-hydroxy-1,4-naphthoquinone has led to promising anticancer agents in which metal complexation with copper­(II) resulted in increased cytotoxicity . The relative stability of the tautomeric forms of 3-(2- R -phenylhydrazono)-naphthalene-1,2,4-trione derivatives (Figure ) is a function of the substituents …”
Section: Copper Complexes As Anticancer Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1,2- and 1,4-naphthoquinone nuclei are commonly encountered in natural products, and their derivatives exhibit a wide range of pharmacological properties including anticancer activities. , Such properties are due to the interference of quinones in the electron transport chain by electron reduction processes, generating semiquinone radical (Q •– ) and hydroquinone anion (Q 2– ). , Incorporation of an azo group into 2-hydroxy-1,4-naphthoquinone has led to promising anticancer agents in which metal complexation with copper­(II) resulted in increased cytotoxicity . The relative stability of the tautomeric forms of 3-(2- R -phenylhydrazono)-naphthalene-1,2,4-trione derivatives (Figure ) is a function of the substituents …”
Section: Copper Complexes As Anticancer Agentsmentioning
confidence: 99%
“…The results indicated that the presence of −NO 2 and −I groups were relevant for the antitumor activity. Formation of an organic free radical observed in the EPR spectrum of [Cu­( L 33o ) 2 ] might be responsible for the cytotoxic activity …”
Section: Copper Complexes As Anticancer Agentsmentioning
confidence: 99%
“…The modification of pharmacologically active compounds may lead to a new finding of novel drugs with diverse pharmacological activities [8]. Chemical modification of aspirin, for instance, has been reported to reduce gastrointestinal toxicity and exhibited diverse biological activities such as anticancer [9], antiinflammatory [10], and antibacterial [11,12] activities. Aspirin 2 Journal of Chemistry bearing active functional groups such as diethyl phosphate and nitro groups has been reported to have anticancer activity against pancreatic and colon cancers [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Nor-β-Lapachone ( 1 ) is a very important naphthoquinone since it has selective cytotoxicity to human lymphocytes, HL-60 leukemia cells and murine fibroblasts V79 [ 11 ]. This compound has been the basis for the synthesis of several important analogues or derivatives with improved biological activities [ 12 , 13 , 14 , 15 , 16 , 17 ]. Recently, it was demonstrated that the modification of the dihydrofuran ring of nor-β-lapachone ( 1 ) could considerably change its activity against cancer cells [ 18 , 19 , 20 , 21 ], Trypanosoma cruzi ( T. cruzi ) [ 22 , 23 , 24 , 25 , 26 ], and candidal agents [ 27 ].…”
Section: Introductionmentioning
confidence: 99%